KONSTRUKSI IDEOLOGIS ISLAM MODERAT DI LINGKUNGAN KAMPUS: STUDI KASUS MA’HAD AL-JAMI’AH UIN SUNAN AMPEL SURABAYA DAN UIN MAULANA MALIK IBRAHIM MALANG - Haris Shofiyuddin (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2019)
The purpose of this article is to find out the position and role of Ma’had al-Ja>mi’ah at The State Islamic University of Sunan Ampel Surabaya and The State Islamic University of Maulana Malik Ibrahim Malang in strengthening the importance of Moderate Islam. In the context of this goal, this paper is expected to contribute to formulating a philosophical frame of mind and its application of Ma'had al-Ja>mi’ah's strategic position as an institution that takes part in strengthening the ideology of Moderate Islam. Practically, this research can be a basis and guideline for all campus stakeholders, both at the State Islamic University of Sunan Ampel Surabaya and the State Islamic University of Maulana Malik Ibrahim Malang, or other campuses regarding the importance of Ma'had al-Ja>mi’ah as a guarded front in supporting the mainstreaming of moderate Islam in the campus environment. In reviewing this matter, researchers used a type of qualitative research with a phenomenological approach. The results of this study are Ma'had al-Ja>mi’ah has played a role in strengthening the ideology of Moderate Islam on campus reflected in daily activities. These activities aim as habituation and also as a strategy, exemplary, and also fosters discipline and build a tolerant character. Besides that there are several activities to realize moderate Muslim attitudes in Ma'had al-Ja>mi'ah, cultural tolerance through fostering tolerant student life, understanding cultural diversity and moreover gaining human nature regardless of social or economic status. Abstrak Tujuan dari artikel ini adalah untuk mengetahui posisi dan peran Ma'had al-Ja>mi’ah UIN Sunan Ampel Surabaya dan UIN Maulana Malik Ibrahim Malang dalam memperkuat pentingnya Islam Moderat. Dalam konteks tujuan ini, tulisan ini diharapkan dapat berkontribusi dalam merumuskan kerangka berpikir filosofis dan penerapannya tentang posisi strategis Ma'had al-Ja>mi’ah sebagai lembaga yang mengambil bagian dalam memperkuat ideologi Islam Moderat. Secara Praktis, penelitian ini dapat menjadi pijakan dan pedoman bagi semua pemangku kepentingan kampus, baik di Universitas Islam Negeri Sunan Ampel Surabaya dan Universitas Islam Negeri Maulana Malik Ibrahim Malang, atau kampus lain mengenai pentingnya Ma'had al-Ja>mi’ah sebagai penjaga depan dalam mendukung pengarusutamaan Islam moderat di lingkungan kampus. Dalam mengkaji hal tersebut peneliti menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologi. Adapun hasil dari penelitian ini adalah Ma'had al-Ja>mi’ah berperan dalam memperkuat ideologi Islam Moderat di kampus yang tercermin dalam kegiatan sehari-hari. Kegiatan ini bertujuan sebagai pembiasaan dan juga sebagai strategi, keteladanan, dan juga menumbuhkan disiplin dan membangun karakter yang toleran. Selain itu ada beberapa kegiatan untuk mewujudkan sikap Muslim moderat di Ma'had al-Ja>mi’ah toleransi budaya melalui menumbuhkan kehidupan mahasiswa yang toleran, memahami keragaman budaya dan juga memahami sifat manusia terlepas dari status sosial atau ekonomi.